Prevalence and associated factors of double and triple burden of malnutrition among child-mother pairs in Ethiopia: Spatial and survey regression analysis - Bethelihem Tigabu Tarekegn; Nega Tezera Assimamaw; Kendalem Asmare Atalell; Selam Fisiha Kassa; Addis Bilal Muhye; Masresha Asmare Techane; Tewodros Getaneh Alemu; Chalachew Adugna Wubneh; Getaneh Mulualem Belay; Tadesse Tarik Tamir; Destaye Guadie Kassie; Amare Wondim; et al. (BMC Nutrition, 2022)
Abstract Background Evidence on double and triple burdens of malnutrition at household level among child-mother pairs is a key towards addressing the problem of malnutrition. In Ethiopia, studies on double and triple burdens of malnutrition are scarce. Even though there is a study on double burden of malnutrition at national level in Ethiopia, it doesn’t assess the triple burdens at all and a few forms of double burden of malnutrition. Therefore, this study aimed to determine the prevalence and associated factors of double and triple burdens of malnutrition among child-mother pairs in Ethiopia. Methods A total sample of 7,624 child-mother pairs from Ethiopian Demographic and Health Survey (EDHS) 2016 were included in the study. All analysis were performed considering complex sampling design. Anthropometric measures and hemoglobin levels of children, as well as anthropometric measurements of their mothers, were used to calculate double burden of malnutrition (DBM) and triple burden of malnutrition (TBM). Spatial analysis was applied to detect geographic variation of prevalence of double and triple burdens of malnutrition among EDHS 2016 clusters. Bivariable and multivariable binary survey logistic regression models were used to assess the factors associated with DBM and TBM. Results The overall weighted prevalence of DBM and TBM respectively were 1.8% (95%CI: 1.38–2.24) and 1.2% (95%CI: 0.83–1.57) among child-mother pairs in Ethiopia. Significant clusters of high prevalence of DBM and TBM were identified. In the adjusted multivariable binary survey logistic regression models, middle household economic status [AOR = 0.23, 95%CI: 0.06, 0.89] as compared to the poor, average birth weight [AOR = 0.26, 95%CI: 0.09, 0.80] as compared to large birth weight and children aged 24–35 months [AOR = 0.19, 95%CI: 0.04,0.95] as compared to 6–12 months were less likely to experience DBM. Average birth weight [AOR = 0.20, 95%CI: 0.05, 0.91] as compared to large birth weight and time to water source <=30 min [AOR = 0.41, 95%CI: 0.19,0.89] as compared to on premise were less likely to experience TBM. Conclusion There is low prevalence of DBM and TBM among child-mother pairs in Ethiopia. Interventions tailored on geographic areas, wealth index, birth weight and child birth could help to control the emerging DBM and TBM at household level among child-mother pairs in Ethiopia.